Rose effect and the Euro: The magic is gone - Tomáš Havránek (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper presents an updated meta-analysis of the effect of currency unions on trade, focusing on the Euro area. Using meta-regression methods such as funnel asymmetry test, evidence for strong publication bias is found. The estimated underlying effect for non-Euro studies reaches about 50%. However, the Euro's trade promoting effect corrected for publication bias is insignificant. The Rose effect literature shows signs of the economics research cycle: reported t-statistic is a quadratic function of publication year. Explanatory meta-regression (robust fixed effects and random effects) suggests that some authors produce predictable results. Interestingly, proxies for authors' IT skills were also found significant.
Keywords: C42; F15; F33; 330; Rose effect; Trade; Currency union; Euro; Meta-analysis; Publication bias; Währungsunion; Euro; Handelseffekt; Bibliometrie; Meta-Analyse